Extending the Spectrum: An in Depth Analysis of the Teaching Styles Taxonomy - Digelidis, Νικόλαος (Inquiries in Physical Education and Sport, 2006)
The aims of the present work was the examination of the relevant research in the spectrum of teaching styles (Mosston, 1966) and the conduction of an in-depth analysis of the theory. The spectrum is a manner of classification of teaching methods based in the dynamics of teaching. Each method provides a frame in which a teacher provides teaching. From 1966 up to the 2002, Mosston and Ashworth, with five publications of their book, advanced in the delimitation of 11 different teaching methods or teaching styles as they named them: from the «command style» where the teacher takes all the decisions in the teaching process, up to «self-teaching style» where all the decisions are taken by the student. However, an extensive in-depth analysis of the teaching styles spectrum theory revealed that it is still under development and needs further clarification in order to integrate teaching methods taxonomy.